Spinal alignment, mobility of the hip and thoracic spine and prevalence of low back pain in young elite cross-country skiers - Alricsson, M.; Björklund, G.; Cronholm, M.; Olsson, O.; Viklund, P.; Svantesson, U. (Journal of Exercise Rehabilitation, 2016)
This study investigated the association between spinal alignment, mobility of the hips and the thoracic spine and low back pain in adolescent cross-country skiers. Cohort of 51 elite cross-country skiers from a cross-country skiing high school in Sweden participated in the study. Sagittal spinal alignment, active range of motion in flexion, extension and rotation of the thoracic spine as well as passive and active extension of the hips were measured. The participants also completed a questionnaire regarding training, competition, skiing technique and occurrence of low back pain. A simple linear regression was calculated to predict pain score based on thoraco-lumbar relation, with a significant (P<0.05) regression equation of y=-0.069x+2.280 (standard error of estimate, 0.034). Participants with greater lordosis than kyphosis were more likely to suffer from low back pain than subjects without this offset. Thoracic mobility and passive or active hip extension showed no correlation with low back pain. Sagittal spinal alignment seems to be related with low back pain among young elite cross-country skiers. This study shows that range of motion of the thoracic spine and hips do not have an effect on the prevalence of low back pain in this population.